OPTIMALISASI RETURN SKEMA INTRADAY TRADING SAHAM SYARIAH INDONESIA MELALUI PEMILIHAN HARI DAGANG - Siti Azizah (Universitas KH. A. Wahab Hasbullah, 2023)
Traders on the stock exchange under any circumstances try to minimize risk and maximize returns, including when the stock market is affected by Covid-19. At that time the Indonesian stock market experienced an extreme decline in stock prices in general. It happened gradually until it formed a downtrend over a fairly long period. Investors and active traders bear the loss of this condition. Wait and see until the downtrend ends is not always a solution. This study provides input for traders by observing in more detail the fluctuations that occur in the daily period which is referred to as the intraday scheme. Assuming whether there are certain days with a more positive tendency for returns than other days. The research was conducted using quantitative methods with a non-experimental approach with descriptive statistical data processing techniques. The results of observations on the 2017-2022 Indonesian Sharia Stock Index (ISSI) data show that Friday is the day that has the most tendency for prices to rise, the biggest returns, and the highest performance index (based on the Sharpe and Treynor Index) than other days. Keywords: return, Covid-19, intraday trading